The Problem of Consent with Teledildonics and Adult Webcam Platforms - Gidaris, Constantine (Surveillance & Society, 2024)
In this article, I examine some of the dangers that are associated with sex toys known as teledildonics. Unlike more conventional sex toys, teledildonics connect to the internet and allow their users and others to control these devices remotely and often through a Bluetooth connection. While teledildonics introduce new ways of engaging and experiencing sexual pleasure, they do so by risking the personal and sensitive data that such devices transmit and collect from their users. Moreover, I consider the risk that teledildonics pose as connected technologies that can be hacked and controlled, scrutinizing what this means in terms of consent and sexual assault in intimate relationships and on a live adult webcam platform like Chaturbate. I investigate how current legal definitions of consent and sexual assault neglect online sex workers, and especially those who work within a tip and token system like Chaturbate, and question how legal protections can be enforced amidst the jurisdictional and territorial problems that plague cyberspace more broadly. With these lack of protections in place, I build on scholarly research that identifies some of the risks that are associated with teledildonics as technologies of potential sexual assault (Nixon 2018; Sparrow and Karas 2020; Arrell 2022). In specific, I study how Canadian laws are ill-equipped to address the more obscure nature of consent and sexual assault as they pertain to Chaturbate and Lovense devices, a leading teledildonics company.